2016
DOI: 10.3390/nu8080489
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Continuous Glucose Monitoring (CGM) during Continuous and High-Intensity Interval Exercise in Patients with Type 1 Diabetes Mellitus

Abstract: Continuous exercise (CON) and high-intensity interval exercise (HIIE) can be safely performed with type 1 diabetes mellitus (T1DM). Additionally, continuous glucose monitoring (CGM) systems may serve as a tool to reduce the risk of exercise-induced hypoglycemia. It is unclear if CGM is accurate during CON and HIIE at different mean workloads. Seven T1DM patients performed CON and HIIE at 5% below (L) and above (M) the first lactate turn point (LTP1), and 5% below the second lactate turn point (LTP2) (H) on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 39 publications
(71 reference statements)
4
47
1
2
Order By: Relevance
“…Although previous research found that the iCGM system was accurate in real-life conditions and may improve glycaemic control [1,2,5,15], during exercise the accuracy of absolute glucose values measured is only moderate and additional finger-prick glucose measurements are required. In comparison to a previous study performing exercise with a similar mean exercise intensity using the Medtronic Enlite TM sensor (Medtronic Diabetes, Northridge, CA, USA) the mean absolute relative difference was found to be 12.8% [16]. However, trend arrows of iCGM providing information about velocity of glucose changes could still be of value during exercise.…”
Section: Discussioncontrasting
confidence: 59%
“…Although previous research found that the iCGM system was accurate in real-life conditions and may improve glycaemic control [1,2,5,15], during exercise the accuracy of absolute glucose values measured is only moderate and additional finger-prick glucose measurements are required. In comparison to a previous study performing exercise with a similar mean exercise intensity using the Medtronic Enlite TM sensor (Medtronic Diabetes, Northridge, CA, USA) the mean absolute relative difference was found to be 12.8% [16]. However, trend arrows of iCGM providing information about velocity of glucose changes could still be of value during exercise.…”
Section: Discussioncontrasting
confidence: 59%
“…One might assume that physical exercise per se did not deteriorate the performance of the flash GM system, because the rate of change in glucose appeared to result in inaccuracy. In the present study, the MARD during exercise was inherently higher than that with other CGM devices such as Minimed 640G (Medtronic), Dexcom G4 Platinum (Dexcom) or Paradigm Veo Enlite (Medtronic) (mean absolute relative difference/MARD, ~18%) . A systematic overestimation of 2.7 mmol/L might suggest that anticipation of intervention to avoid exercise‐induced hypoglycaemia is required as soon as an interstitial glucose level of 7.2 mmol/L is reached.…”
Section: Discussionmentioning
confidence: 52%
“…While CGM provides a cost effective [ 36 ] way to continuously monitor interstitial glucose levels of patients in a practical or research setting [ 37 ], its accuracy during various forms of exercise has occasionally been questioned, and is thus still under investigation [ 38 , 39 , 40 , 41 , 42 ]. With improvements in sensor technology and device-related algorithms, CGM systems have rapidly improved their accuracy over the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…With improvements in sensor technology and device-related algorithms, CGM systems have rapidly improved their accuracy over the past decade. During that time, studies have assessed CGM accuracy during continuous aerobic [ 39 , 40 , 41 , 42 ], high intensity interval [ 39 , 40 ], and resistance exercise [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation